2014
DOI: 10.1109/jphotov.2013.2280340
|View full text |Cite
|
Sign up to set email alerts
|

Light Trapping Textures Designed by Electromagnetic Optimization for Subwavelength Thick Solar Cells

Abstract: Light trapping in solar cells allows for increased current and voltage, as well as reduced materials cost. It is known that in geometrical optics, a maximum 4n 2 absorption enhancement factor can be achieved by randomly texturing the surface of the solar cell, where n is the material refractive index. This ray-optics absorption enhancement (AE) limit only holds when the thickness of the solar cell is much greater than the optical wavelength. In subwavelength thin films, the fundamental questions remain unanswe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 45 publications
(59 reference statements)
4
58
0
Order By: Relevance
“…It is well known that the texturing of solar cell surfaces enhances the light absorption that results from the coupling of incident light rays to totally internally reflected modes within the cell [30]. Therefore, textured Ge surfaces observed in the current study were expected to increase the amount of absorbed light, which allows for improved performance when they were applied to solar cells.To maximize the light absorption effect of surface texturing, the dilute H 2 O 2 and FPM compositions that yielded the greatest RMS surface roughness and surface area among those studied were used: dilute H 2 O 2 of 30% H 2 O 2 /H 2 O = 1/99 v/v, used for 30 min, and 4/5/1 FPM, used for 1 min.…”
Section: Effect Of Ge Mace On Solar Cell Performancementioning
confidence: 82%
“…It is well known that the texturing of solar cell surfaces enhances the light absorption that results from the coupling of incident light rays to totally internally reflected modes within the cell [30]. Therefore, textured Ge surfaces observed in the current study were expected to increase the amount of absorbed light, which allows for improved performance when they were applied to solar cells.To maximize the light absorption effect of surface texturing, the dilute H 2 O 2 and FPM compositions that yielded the greatest RMS surface roughness and surface area among those studied were used: dilute H 2 O 2 of 30% H 2 O 2 /H 2 O = 1/99 v/v, used for 30 min, and 4/5/1 FPM, used for 1 min.…”
Section: Effect Of Ge Mace On Solar Cell Performancementioning
confidence: 82%
“…for thin-film photovoltaic). The working principle of our samples is similar to of textured surfaces 9,10 with the additional feature of resonances mediating the light coupling. In view of applications of our AR on thin-film photovoltaic cells or light detectors, the merit of our method is to avoid a direct texturing of the Si wafer thus potentially preserving a high carrier mobility and lifetime 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Efficient anti-reflection coatings (AR) have been intensively studied with many different approaches having been explored for this purpose [1][2][3] , such as multi-layered thinfilms 4,5 , graded index matching via surface texturing with micro-and nano-structures [6][7][8][9][10][11] , plasmonic metasurfaces [12][13][14] and more recently, metasurfaces [15][16][17][18][19][20][21] based on ordered arrays of sub-micrometric dielectric antennas (dielectric Mie resonators [22][23][24][25][26][27][28] ). Depending on the application of the AR different aspects (lowest value of the total reflectance, broad spectral range, broad acceptance angle, transparency or light trapping) determine the optimal features and fabrication method.…”
Section: Introductionmentioning
confidence: 99%
“…3,4) Novel concepts for efficient light confinement have been studied, especially in a subwavelength regime. [5][6][7][8][9][10] Another way to improve light absorptance is to introduce a silicon nanowire (SiNW) array as a light absorption layer. Many researchers have reported that SiNW arrays have high light absorptance and are promising as absorber layers for solar cells.…”
Section: Introductionmentioning
confidence: 99%